Quantitative analysis of water vapor budget of a persistent rainstrom event in Tongren of Guizhou Province - Chunyan LV; Jun CHEN; Yimeng LIU; Qun YANG; Nan XIANG; Qing FU (暴雨灾害, 2023)
This paper focus on revealing the features of the water vapor transport, water vapor budget and the contribution percentage of water vapor source regions of the persistent rainstorm in Tongren from July 13th to 16th, 2014 based on precipitation observation data, ERA5 and NCEP GDAS (National Centers for Environmental Prediction, Global Data Assimilation System) reanalysis data and the HYSPLIT4 (Hybrid Single-Particle Lagrangian Integrated Trajectory Model) mode. The results show that: (1) the eastward South Asian High and coupling mechanism of high and low level jets enhanced the dynamic mechanism of convergence at low level and divergence at high level which is conducive to the convergence of water vapor in the target region to condense and then form precipitation. (2) The water vapor over the ocean was continuously transported to the rainstorm area by the water vapor channel built by the synergistic effect of the subtropical high which table controlled the south of Guizhou province, shortwave trough lay the northwest side of subtropical high, and tropical cyclone in the Indian Peninsula at 500 hPa. (3) The air particles in the rainstorm area mainly came from the Arabian Sea, the Bay of Bengal and the South China Sea at a lower height, while a few particles came from the north of Tongren to Eurasia, the Atlantic Ocean at a higher height by 120 h backward trajectory simulation. (4) The contribution percentage of water vapor source regions of the south of Tongren-South China Sea and its nearby islands and water, the east of the Indian Peninsula-the Bay of Bengal, the Arabian Sea-the west of the Indian Peninsula were 48.29%, 32.17 % and 10.47% respectively. In addition, the water vapor the north of Tongren to Eurasia and the Atlantic Ocean also contributed to the rainstorm in Tongren (9.07%). (5) 850 hPa and 700 hPa were the main water vapor contribution levels which provided nearly 3/4 of water vapor to the rainstorm area, the remaining quarter was transported by 500 hPa.